Kedudukan Hukum Tanah Adat Pelaba Pura sebagai Tanah Ulayat di Desa Tampaksiring Kabupaten Gianyar - Ida Bagus Nyoman Trisya Andika; I Wayan Wesna Astara; I Putu Gede Seputra (Warmadewa Press, 2021)
Bali as a province with strong customs also has several binding customary laws. The status of ulayat land still lacks legal protection. There are still many villagers who do not take care of the temple land or in the status of their ulayat land which is legal. This study aims to determine the existence of pelaba pura customary land as communal land in the village of Tampaksiring, Gianyar district by law of agrarian law and to analyze the implementation of the legal position of the pelaba pura land in Tampaksiring Village, Gianyar Regency. This study uses empirical legal research with a statutory approach. The source of law is primary legal materials, namely using legal materials that are studied using specifically applicable regulations, while secondary legal materials are based on literature, articles, journals and related to problems. The results showed that the process of resolving the land certification of pelaba pura land in Tampaksiring Village, Gianyar Regency was by using the customary offense sanction, namely by fencing the land according to the results of the customary paruman that had been implemented. Finally, the land was voluntarily handed back to the temple. The legal position of the temple's pelaba land in Tampaksiring Village is an important matter that must be considered because there are still many suspected cases that have occurred in Balinese society, especially in Tampaksiring Village. In land disputes, the temples in Tampaksiring refer to customary law where the sanctions imposed on land certifiers are sanctions that have been agreed upon and regulated in local customary law.